The Influence of Technology-Based Instruction on Student Learning, Motivation and Teacher Perceptions Toward Science Instruction - Gaddy, Janet S. (Valdosta State University, 2007)
The purpose of the research study was to determine the impact of technology resources, specifically WebQuests, streaming videos, and laboratory manipulatives for science classroom instruction on student achievement. Student and teacher perceptions of the use of technology resources to learn the science objectives were also examined. Three research questions were posed: (a) How does the use of technology resources, specifically WebQuests, streaming videos, and laboratory manipulatives for science classroom instruction, influence student achievement? (b) How does the use of technology resources, specifically WebQuests, streaming videos, and laboratory manipulatives for science classroom instruction, influence student motivation to learn science? (c) What are the teacher perceptions about the use of technology, specifically WebQuests, streaming videos, and laboratory manipulatives for science classroom instruction? Participants in this research study included 19 seventh-grade students ranging in age from 12-14. The research study extended over a three-week period. Science achievement tests, attitudinal surveys, and a teacher journal were analyzed to determine the influence that the various technologies had on student achievement, student perceptions of science and teacher perceptions of using technology to teach a unit of study. Data show that the use of varied technology greatly improved student achievement and their perceptions toward science. The teacher perception was also improved based on the observations used throughout the process. Information was presented to the learning community and discussions were held to create a dialogue to enhance the use of technology in the classrooms through the use of WebQuests, streaming videos, and laboratory manipulatives.
Keywords: Technology resources; WebQuests; Science instruction; Student achievement; Educational technology; Teaching--Aids and devices; Computer-assisted instruction